Locke and the legislative point of view : toleration, contested principles, and law - Tuckness, Alex Scott, 1971- (Princeton University Press, 2002)
Determining which moral principles should guide political action is a vexing question in political theory. This is especially true when faced with the "toleration paradox": believing that something is morally wrong but also believing that it is wrong to suppress it. In this book, Alex Tuckness argues that John Locke's potential contribution to this debate--what Tuckness terms the "legislative point of view"--Has long been obscured by overemphasis on his doctrine of consent. Building on a line of reasoning Locke made explicit in his later writings on religious toleration, Tuckness explores the